METHODOLOGICAL PROBLEMS OF RESEARCHING THE PRESIDENTIAL INSTITUTE: THE EXPERIENCE OF WESTERN SCIENTISTS IN THE BREAK OF THE CENTURY - KARMAZINA, Mariia (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
Abstract. One of the leading institutions of state power in the world is the institution of the presidency. The history of its study goes back decades (in Europe, Asia, LatinAmerica), and even centuries (for example, in the USA). The attention of researchers to the specifics of the functioning of the presidency became especially relevant with the collapse of the USSR, Yugoslavia, and Czechoslovakia and the emergence of new states, many of which became presidents. The article, based on the methods of selection, comparison (of cross-national and cross-temporal studies of scientists) and generalization of the results of the study of individual cases of the functioning of the presidency institute (presented in the English-language literature), analyzes the development of the logic of its research, as well as directions for expanding the subject field of scientific analysis; methodological approaches, specific method sused by Western researchers of the presidential institute are singled out; a number of issues have been clarified, without studying which there will be a lack of understanding of the essence of the institute and its development prospects, including in Ukraine. It is established that: despite the long history of the institution of the presidency (in particular, in the USA) and the constant attention of researchers to it, only in the second half of the 20th century did a peculiar break through in the study of the presidency take place. One of the dominantev idences of this was the appearance of the work of R. Neustadt, the feature of which was the analysis of the presidency from a new angle (with posing new questions using new research methods and the emergence of new evaluation accents regarding the effectiveness of presidential decisions); at the end of the 20th – at the beginning of the 21st century. There was a significant expansion not only of the subject field of research on the institution of the presidency (including duet othe in creased attention of scientists to the study of semi-presidential forms of government), but also the development of the theoretical and methodological basis of the analysis (based on neo-institutionalis mand, above all, on the theory of rational choice, streng thening research interest in the application of empirical institutionalism, etc.); in the end, a kind of analytical «going beyond the borders of the West» took place: studies devoted to the study of presidential regimes outside «old Europe» and the USA (inparticular, in Ukraine) began to appear; among the problematic issues of the analysis of the institution of the presidency, which will require the intellectual effort of researchers in the future, there are those related to the instability of analytical definitions (for example, «semi-presidency», «semi-presidential form of government», etc.), with the absence of generally accepted algorithms (strategies) research and «measurement» of the effectiveness of the institute, with an excellent (to date) depth of analysis of the presidency invarious countries (outside of Western Europe and the USA).